SIMULATION DESIGN OF AUTOMATIC CONTROL ROOM LIGHTS - Wishnu Prasati; Triyono, MSC Triyono, MSC (Jurnal Sistem Komputer, 2000)
To be an efficient use of electricity doperlukan a tool that can control and regulate theuse of electric current by way of determining when power consumption is requiredand when the timing is not needed is to add a timer or a timer on the apparatus.For this purpose appropriate media to be utilized is to use the computer as a tool inthe media deemed appropriate and simplify the operation of the simulation controlroom lighting that will be discussed.To apply in accordance with the desired computer, software or software here alsoplay an important role. High-level programming language with ease inimplementation problems. Programming language to be used is Borland Delphi 3.0programming language similar to Pascal.The software will be created is expected to control and regulate or pewaktuyangTimer can be set manually on the computer and then apply it to the interface andcircuit simulation equipment room has been created.